2018
DOI: 10.1093/pubmed/fdy060
|View full text |Cite
|
Sign up to set email alerts
|

Cross-associations between physical activity and sedentary time on metabolic health: a comparative assessment using self-reported and objectively measured activity

Abstract: Using accelerometer data, the inactive/sedentary group was at higher risk for 1+ disease and abdominal obesity only, whereas the active/sedentary and inactive/non-sedentary groups were not at higher risk for any health outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
1
0
3
Order By: Relevance
“…Importante, la inactividad física y el comportamiento sedentario son factores de riesgo independientes asociados a mortalidad 8 . De hecho, una persona puede ser al mismo tiempo físicamente activa (cumple las recomendaciones de actividad moderada y/o vigorosa) y sedentaria (acumula > 8 h/d de comportamiento sedentario) 11 . Es por ello esencial diferenciar inactividad física y sedentarismo para establecer los riesgos para la salud de la población.…”
unclassified
See 2 more Smart Citations
“…Importante, la inactividad física y el comportamiento sedentario son factores de riesgo independientes asociados a mortalidad 8 . De hecho, una persona puede ser al mismo tiempo físicamente activa (cumple las recomendaciones de actividad moderada y/o vigorosa) y sedentaria (acumula > 8 h/d de comportamiento sedentario) 11 . Es por ello esencial diferenciar inactividad física y sedentarismo para establecer los riesgos para la salud de la población.…”
unclassified
“…yor prevalencia de síndrome metabólico11 . Importante, las personas inactivas/sedentarias -ademáspresentaron mayor prevalencia de enfermedades crónicas, obesidad, obesidad abdominal, presión arterial elevada, glicemia elevada, trigliceridemia elevada, y HDL-C disminuido11 . Estos resultados demuestran como la combinación de los factores de riesgo asociados al patrón de actividad perjudican la salud.…”
unclassified
See 1 more Smart Citation
“…The literature shows that the monitoring of patients' mobility in an inpatient setting can give information similar to advanced and time-consuming techniques, such as behavioral mapping, and it can be useful to collect the activity levels of hospitalized patients [31]. A lower level of activity during hospitalization can lead to a loss of muscle quantity and quality and can seriously hurt the rehabilitation process and patient's health conditions [32][33][34]. A review on wearable sensors for the quantification of, and feedback on, lower extremity movement found that there may be substantial clinical benefits, with more work needed with respect to natural environments and longer monitoring periods [35].…”
Section: Introductionmentioning
confidence: 99%